Representações sociais de crianças negras sobre a cor no contexto escolar em Bragança-Pa - CORRÊA, Antonio Matheus do Rosário (2021)
This study analyzes the social representations of black children about color in the school context. The research is a qualitative approach, applying field research through participant observation (field diary) and focus group interview, which used the dynamics of the dolls, storytelling and projective technique, with 17 children from a school from Bragança-PA. Data analysis was performed using the Theory of Social Representations based on Moscovici (1978) and Bakhtin's discursive dialogism (2011). The theoretical framework is based on Silva (2007), Gomes (2005), Ianni (2004), Santos (2009), among others, to deal with race relations; Feitosa (2012), Gomes and Araújo (2014), Del Priore (2012, 2015), for the discussion about black children in Brazil. The results reveal the presence of racial stigmas and stereotypes in the social representations of children, as well as racism in daily school life. The children seek to assign representations by self-categorization and of skin color graduation, that is the social sense in own social groups. The conclusion in this work is the social representations about color in the school context significantly influence children's attitudes and discourses, causing reproduction of racist practices and recognition of belonging to racial groups.